Laser safety : tools and training - Barat, Ken (Optical science and engineering (CRC Press), 2014)
"Lasers perform many unique functions in a plethora of applications, but there are many inherent risks with this continually burgeoning technology. Laser Safety: Tools and Training, Second Edition presents simple, effective ways for users in a variety of facilities to evaluate the hazards of any laser procedure and ensure they are following documented laser safety standards. Designed for use as either a standalone volume or a supplement to Laser Safety Management, this text includes fundamental laser and laser safety information and critical laser use information rarely found in a single source. Written by a working Laser Safety Officer (LSO), the book's depth and breadth make it appropriate for both the seasoned professional and the novice. It presents case studies of real accidents, preventive measures that could have been taken to avoid such accidents, and templates for documenting potential laser risks and attendant safety measures. Reflecting the exponential use of laser technology over the last several years, this text considers the growing use of petawatt laser installations and nanotechnology applications and addresses current laser projects such as the National Ignition Facility (NIF) and Linac Coherent Light Source (LCLS). Several chapters explore the components of laser work and laser safety that deal with optics, the optical table, the power meter, and user training. The second edition includes coverage of the following new topics:Terahertz radiationLaser safety cultureOptical acceleratorsNanotechnology and laser applicationsLaser lab design lessonsLaser disposal"--